PROSPECTS FOR ESTABLISHING THE RIGHTS OF PERSONS WHO HAVE REPORTED CORRUPTION OFFENSES IN THE REPUBLIC OF UZBEKISTAN - Majidov Shakzod (Scholar Express Journals, 2024)
This article analyzes the prospects for establishing the basic rights of persons who have reported corruption offenses.
Keywords: Corruption; reporting persons; psychological assistance